Neotype designation for Sphingius thecatus Thorell 1890 synonymies new records and descriptions of six new species from Southeast Asia(Araneae Liocranidae) - Dankittipakul P. (2014)
A neotype is designated for Sphingius thecatus Thorell, 1890, the type species of the genus from type locality of Penang Island, Malaysia; its conspecific female is described for the first time. Detailed morphological descriptions and illustrations for both sexes are provided. Six new species are described from Southeast Asia: S. rama sp. nov. and S. prolixus sp. nov. from eastern Thailand; S. elongatus sp. nov. from southern Thailand; S. superbus sp. nov. and S. bifurcatus sp. nov. from Thailand and Malaysia; S. spinosus sp. nov. from Thailand, Malaysia and Indonesia. Sphingius pingtung Tso et al., 2005 known from Taiwan, China is considered a junior synonym of S. scrobiculatus Thorell, 1897. Sphingius sinensis (Schenkel, 1963), originally placed in Scotophaeoides (Gnaphosidae), is regarded as a junior synonym of S. gracilis (Thorell, 1895). Additional specimensof S. gothicus Deeleman-Reinhold, 2001 were collected from northeastern and central Thailand, expanding species distribution range towards the south. Specimens of S. punctatus Deeleman-Reinhold, 2001 were collected from Thailand and Indonesia. Sphingius vivax(Thorell, 1897) and S. scrobiculatus Thorell, 1897 are recorded from Thailand for the first time. © 2011 Magnolia Press.